Civic engagement, youth socialisation and participation in public spheres in Indonesia. (December 2020) - Saud, Muhammad
Highlights: This research is valuable for further research to design civic engagement activities in universities. The study endorsed the significant importance of youths to practice civic activities in their daily routine. It is useful to analyses the perceptions of Indonesian youths on civic engagement, and civic behavior. Abstract: Commitment to youth's development for civic engagement activities across the globe varies considerably. The present study was conducted in a few universities of Indonesia to find out the role of civic socialisation and civic behaviour in order to enhance the civic engagement activities. The study opted the quantitative research design to collect the data from the fields. A research instrument was prepared online to gather the data and multiple responses from the diverse socio-economic population "the youth". The study concludes, youth in Indonesia have learned civic education from schooling, such as from a national subject " Pancasila " which gives a sense of civic education for encouraging youth to participate in civic matters. There are multiple socialisation agents such as family, friends, teachers, and the local environment, which give rise and support to involvement of youth as a civically responsible citizen.